10 - Book Reviews: Maria Nzomo, Women in Top Management in Kenya, Nairobi, African Association for Public Administration and Management, 1995, iii+91p.: by Hannington Ochwada - Hannington Ochwada, (Africa Development, 1997)
Abstract